2020
DOI: 10.1136/jech-2020-214402
|View full text |Cite
|
Sign up to set email alerts
|

Academic performance, subsequent socioeconomic status and suicide attempt in adulthood: path analyses on Swedish cohort data

Abstract: BackgroundPoor academic performance in childhood is associated with suicide attempt in adulthood, but the mechanisms are not known. We investigated educational attainment as a possible pathway.MethodsWe followed two sets of cohorts, born around 1950/1970, respectively, in the Swedish population-representative ‘Evaluation Through Follow-up’ study for a first suicide attempt in national records up to 2013. Data on grade point average (GPA) at age 13/16 and educational attainment (years of schooling) in adulthood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…O alto nível de exigência por parte das instituições, associado ao excesso de conteúdo e diminuição do tempo de lazer são fatores agravantes e, até mesmo, desencadeantes do processo de ideação suicida (CERQUEIRA; SOUZA, 2022). Esses elementos, ainda, prejudicam o rendimento acadêmico dos estudantes, o qual leva essas pessoas a um processo de depressão e, posteriormente, a pensamentos suicidas, configurando-se como mais um fator de risco (WALLIN, 2020;CRISPIM, 2021).…”
Section: Resultsunclassified
“…O alto nível de exigência por parte das instituições, associado ao excesso de conteúdo e diminuição do tempo de lazer são fatores agravantes e, até mesmo, desencadeantes do processo de ideação suicida (CERQUEIRA; SOUZA, 2022). Esses elementos, ainda, prejudicam o rendimento acadêmico dos estudantes, o qual leva essas pessoas a um processo de depressão e, posteriormente, a pensamentos suicidas, configurando-se como mais um fator de risco (WALLIN, 2020;CRISPIM, 2021).…”
Section: Resultsunclassified
“…Workers' mental health was measured through diagnosed CMD (depression, anxiety, and stress-related disorders; ICD-10 codes F32, F33, F41, F43), and alcohol and substance use disorders (ICD-10 codes F10-F19) reported in the in-and outpatient registers during the follow-up period (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016). Like previous studies, only suicide attempts (ICD-10 codes X60-X84 and Y10-Y34) reported in the inpatient register were included (27,28). Both registers are national and comprehensive of the Swedish population.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies investigated the association between cognitive skills and suicide attempt (Alati et al, 2009;Batty et al, 2010;Hansson Bittar et al, 2019;Kosidou et al, 2013;Kosik et al, 2017;Osler et al, 2008;Sorberg Wallin et al, 2020;Sorberg Wallin et al, 2017;Sourander et al, 2009), while 16 studies investigated the association with suicide mortality (Alaraisanen et al, 2006;Andersson et al, 2008;Batty et al, 2009;Bjorkenstam et al, 2010;Calvin et al, 2017;Geoffroy et al, 2014;Gravseth et al, 2010;Gunnell et al, 2011;Gunnell et al, 2005;Hansson Bittar et al, 2019;Richard-Devantoy et al, 2021;Sourander et al, 2009;Webb et al, 2010;Weiser et al, 2015;Werbeloff et al, 2009).…”
Section: Risk Of Suicide Attempt and Suicide: Narrative Synthesismentioning
confidence: 99%
“…Seven out of 10 studies reported an association between lower childhood cognitive skills and increased risk of suicide attempt in adulthood (Alati et al, 2009;Batty et al, 2010;Hansson Bittar et al, 2019;Kosidou et al, 2013;Osler et al, 2008;Sorberg Wallin et al, 2017), while three studies did not find evidence for this association (Kosik et al, 2017;Sorberg Wallin et al, 2020;Sourander et al, 2009). Sorberg Wallin et al (2020) and Sorberg Wallin et al (2017) found that attained education and GPA, respectively, mediated the association between IQ and suicidal behavior (see Table S2 for a summary of mediators, moderators, and confounding factors investigated in the included studies).…”
Section: Risk Of Suicide Attempt and Suicide: Narrative Synthesismentioning
confidence: 99%